Guía para la elaboración de planes maestros de las Zonas de Agrobiodiversidad - Sotomayor Melo, Diego Alejandro; Amasifuen Guerra, Carlos Alberto; Gallardo Meneses, Maruja Elena (Instituto Nacional de Innovación Agraria, 2022)
47 páginas